SKILL OF CRITICAL THINKING FOR HIGH SCHOOL STUDENTS IN SOLVING WRITTEN TEST (UKT) IN BIOLOGY SCIENCE OLYMPIAD for JUNIOR-SENIOR HIGH SCHOOL IN RIAU 2014 - Shania Parvati Janes Parvati Janes; Darmawati '; R. Hussien Arief Hussien Arief (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research was to find outskill of critical thinking for high school students in solving written test in biologyl science olympiad for junior-senior high school in Riau 2014. This research was descriptive research. This reseach conducted in August 2014. The sample of this research were all participants of written test stage II and stage III, participants in UKT stage II were 266 and participants in UKT stage III were 147. Techniques to determine sampling was total sampling. Parameters measured were skill of critical thinking students which used indicators in 5 critical activity of Ennis. The result showed skill of critical thinking of high school students in solving written test stage II and stage II showed not good criteria with percentage respectively 37% and 28.3%. There are 5 critical activity indicators according to Ennis, the research indicated the lowest percentage found in critical activity 4 that provide further explanation. The conclusion of the research was skill of critical thinking high school students in solving written tes in biology science olympiad for Junior-Senior high school students in Riau 2014 was not good with percentage 32.65%. Keywords: Critical Thinking, Written Test, Biology Science Olympiad